Reproductive biology of the yellow snapper, Lutjanus argentiventris (Pisces, Lutjanidae), from the Mexican central Pacific - Gabriela Lucano-Ramírez (Ciencias Marinas, 2014)
The yellow snapper, Lutjanus argentiventris, is a commercial species along the Pacific coast, yet few studies have been carried out on its reproductive biology. Monthly samplings of the artisanal fishery off the coast of Jalisco, Mexico, were made from 1998 to 2008. Mean total length and weight of analyzed specimens were 32.6 cm (±0.13) and 567.3 g (±9.15), respectively. A total of 945 females (50.3%) and 932 males (49.7%) were collected; the overall sex ratio was 1:0.99. The highest percentages of mature fish were obtained between July and October. The highest gonadosomatic index values (1.46 to 0.81) and highest oocyte diameters were also obtained during that period. For this reason the period from July to October is considered the breeding season of L. argentiventris. This species presented asynchronous ovarian development and seven stages of oocyte development were identified. The testis showed lobular development and in the ripe stage, sperm were observed in the center of the lobes and in the main duct. Mean size at sexual maturity (L50) was 31.6 cm for females and 31.4 cm for males, and there was no significant variation in L50 among years. Due to the long period of study, this information could be used to establish measures for the proper exploitation of the species.